2017
DOI: 10.1007/s10584-017-2089-7
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of political affiliation in the link between flooding experience and preparedness to reduce energy use

Abstract: Research suggests that highlighting links between local weather events and climate change can help promote climate change engagement. Yet, the evidence for the relationship between weather experiences and climate change attitudes has been mixed. Here we argue that obtaining an accurate assessment of the contribution of weather experiences to climate change engagement necessitates explicit evaluation of factors such as values and identities that influence the way weather experiences are interpreted and integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 54 publications
1
27
1
Order By: Relevance
“…This study also reiterates evidence of a link between political affiliation and climate change perceptions insofar that right-leaning voting intention was shown to negatively predict attribution of the 2013/2014 UK flooding to climate change. This finding is consistent with previous suggestions by Ogunbode et al (2017) that flooding perceptions and associated responses to climate change in the UK covary systematically with individuals' political affiliation. Affiliation with the right-leaning Conservative Party has previously been linked with climate change scepticism (Whitmarsh, 2011), and political group identity can be expected to influence whether individuals perceive relevant events to be unusual, unnatural and a reason to worry or act (Hahnel and Brosch, 2016;Shao and Goidel, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study also reiterates evidence of a link between political affiliation and climate change perceptions insofar that right-leaning voting intention was shown to negatively predict attribution of the 2013/2014 UK flooding to climate change. This finding is consistent with previous suggestions by Ogunbode et al (2017) that flooding perceptions and associated responses to climate change in the UK covary systematically with individuals' political affiliation. Affiliation with the right-leaning Conservative Party has previously been linked with climate change scepticism (Whitmarsh, 2011), and political group identity can be expected to influence whether individuals perceive relevant events to be unusual, unnatural and a reason to worry or act (Hahnel and Brosch, 2016;Shao and Goidel, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Right-leaning voters were the focus in the current analyses (with the reference category being 'other' voters) because they may be more likely to conform with the norms of their political in-group (Panagopoulos and van der Linden, 2016). This focus also derives from a desire to further explore reasons why flooding experiences may have a weaker link with climate change mitigation responses among right-leaning UK voters (see Ogunbode et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners disagreed on the community desire to incorporate climate adaptation practices into flood mitigation planning, which may reflect the politically contentious nature of climate change in US political discourse and policymaking more generally. Previous research has demonstrated disconnections between public climate-flood risk perceptions and expert opinion (e.g., Hamilton et al, 2016;Ogunbode et al, 2017;Shepard et al, 2018). In this case study, professionals disagreed on both community perceptions (Table 4) and climate education (Table 5).…”
Section: Perceptions Of Climate-weather-flood Linkages and Climate Admentioning
confidence: 60%
“…A conceptual disconnect on the definition of flooding points to issues with the core problem statement that coalitions of flooding professionals are self-organized to solve. While formal guidelines exist at the US national level (Obama, 2015), these definitions often conflate risk and hazard. Formal federal definitions in the USA commonly focus on hydrologic hazard posed by a static water surface elevation, as in FEMA flood insurance rate maps (FEMA, 2018), neglecting hazard associated with discharge velocity, duration of inundation, and suspended material.…”
Section: Definitions and Extents Of Floodingmentioning
confidence: 99%